2020
DOI: 10.18203/2349-3291.ijcp20201040
|View full text |Cite
|
Sign up to set email alerts
|

A study to determine the level of cord blood albumin in predicting neonatal jaundice

Abstract: Background: Most unconjugated bilirubin formed by the fetus is cleared by the placenta into the maternal circulation. Albumin constitutes 70 - 75% of Plasma oncotic pressure. Another important function of albumin is its antioxidant property. Bilirubin binds to albumin in an equimolar ratio. Free bilirubin is anticipated when the molar bilirubin- to- albumin (B: A) ratio is >0.8 Objective of the study was to predict the proportion of newborn requiring intervention for NH (phototherapy or exchange transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this study we have found that there is no gender predilection for the development of NH (p=0.122) which was supported by most of the studies. 18,19,[26][27][28][29]31,33 In this study, study group is uniformly distributed with 60 male and 82 female babies. There is no significant correlation (p=0.122) in the TSB levels and the sex of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have found that there is no gender predilection for the development of NH (p=0.122) which was supported by most of the studies. 18,19,[26][27][28][29]31,33 In this study, study group is uniformly distributed with 60 male and 82 female babies. There is no significant correlation (p=0.122) in the TSB levels and the sex of the newborn.…”
Section: Discussionmentioning
confidence: 99%